Development of a Giant Magnetostriction-Type Ultraprecision Positioning Device and Ultraprecision Machine Tool Equipped with It - Hamada, Ryuji; Eda, Hiroshi; Sasaki, Yasuhiko (Transactions of the Japan Society of Mechanical Engineers Series C, 1994)
A giant magnetostriction-type ultraprecision positioning device (GMUPD) was manufactured from newly developed giant magnetostriction materials with compositions of Tb1-xDyx(FeyMn1-y)n. The output power of them is several times and the displacement is several ten times that of PZT without a magnifier. An ultraprecision machine tool was developed with the present GMUPD. The workpiece can be fed at a rate of 0.1 mm/min or 600 mm/min and is cut by a turning diamond tool. The hard and brittle materials such as glass and ceramics were finished in the ductile mode, and surface roughness was obtained within several nanometers.